Brazilian Sign Language in health: Evaluation from the perspective of patients and medical students (Research, Society and Development, 2021)
Objective: To investigate the expansion of knowledge about the need for access to health services for people with hearing loss. Methodology: This is a quantitative study with a descriptive and cross-sectional study design and is part of the Libras em Saúde project of the NGO International Federation of Medical Students Association of Brazil, committee of the Federal University of Pará, whose general objective is to investigate the assistance to deaf people in the health field from an academic perspective and also from the deaf person’s perspective. Results: The percentage of negative evaluations of the meeting with health professionals represented 51% among bilinguals; and 78% in the group of deaf people who communicate. 56 academics from the third and fourth years of medicine at UFPA were interviewed. The pre-test showed the students' lack of knowledge about deaf culture and Brazilian sign language (Libras). In the post-test: the students were able to differentiate the deaf from the person with hearing loss by insertion or not in the deaf culture. Conclusion: Deaf patients use the health system differently from hearing patients and report difficulties represented by fear, distrust and frustration. The study demonstrates that health professionals are not prepared to deal with the care of people with hearing impairments, also referring to the lack of interpreters to assist in these services and the lack of patience in conducting procedures through professionals. Thus, the inclusion of teaching Brazilian language (Libras) as a discipline of the medical course, becomes an important instrument of change in the social reality that the hearing impaired is currently included.